Naming Food With The Word "Setan" Or With Negative Names In The Perspective Of Islamic Law - Hayati, Fauziyah; Madinah, Nuril; Lesmana, Muhammad Andy; Putra, Muhammad Rayhan; Hamed, Nassem; Fadillah, Rahmat (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
The naming of food is very influential on public interest in food products, the sellers compete to provide attractive names that describe the taste of the food. However, many of the sellers do not know the law of naming a food with negative things like the word "devil". It is the aim of this study to review why this is prohibited and whether people are aware of the law on naming food with the word "satan". The method used in this study is a qualitative descriptive method, namely the source of the discussion is obtained from zinterviews and literature studies. From the results of this study it can be concluded that the naming of food with bad words such as "satan" is prohibited because it has a negative meaning, except for food names that have become a tradition ('urf) with the condition that they do not contain haram ingredients. Keywords: Food Names, Satan, Islamic Law